2016
DOI: 10.1038/srep20723
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 Fatty Acid, α-Tocopherol, Zinc, vitamin D, vitamin C and β-carotene are Associated with Age-Related Macular Degeneration in Japan

Abstract: This case-control study reports the association between nutrient intake and neovascular age-related macular degeneration (AMD) in Japan. The nutrient intake of 161 neovascular AMD cases from two university hospitals and 369 population-based control subjects from a cohort study was assessed using a brief-type self-administered questionnaire on diet history, which required respondent recall of the usual intake of 58 foods during the preceding month. Energy-adjusted nutrient intake values were compared between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…Our findings that AMD cases had lower intakes of vitamins C and E and beta-carotene concur with a recent Japanese case–control study,21 which also showed significant differences in dietary intake of vitamins C and E and beta-carotene between patients with AMD and healthy controls. AREDS demonstrated that intake of high doses of vitamins C and E and beta-carotene alone was not sufficient, but rather required the addition of zinc to reduce the risk of neovascular AMD,5 and the high dose of vitamin E (400 IU) recommended by AREDS is likely to be only achieved by vitamin E supplementation 21.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings that AMD cases had lower intakes of vitamins C and E and beta-carotene concur with a recent Japanese case–control study,21 which also showed significant differences in dietary intake of vitamins C and E and beta-carotene between patients with AMD and healthy controls. AREDS demonstrated that intake of high doses of vitamins C and E and beta-carotene alone was not sufficient, but rather required the addition of zinc to reduce the risk of neovascular AMD,5 and the high dose of vitamin E (400 IU) recommended by AREDS is likely to be only achieved by vitamin E supplementation 21.…”
Section: Discussionsupporting
confidence: 92%
“…AREDS demonstrated that intake of high doses of vitamins C and E and beta-carotene alone was not sufficient, but rather required the addition of zinc to reduce the risk of neovascular AMD,5 and the high dose of vitamin E (400 IU) recommended by AREDS is likely to be only achieved by vitamin E supplementation 21. Our results therefore reinforce the importance of all the micronutrients and antioxidants in the AREDS formulation in reducing rates of progression of late AMD.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Zinc is a cofactor of many active ocular enzymes, including superoxide dismutase and catalase [8, 72]. Zinc also binds complement factor H, inducing large multimeric forms that loose complement 3b inhibitory activity [73].…”
Section: Zinc Supplementationmentioning
confidence: 99%
“…For example, in Japan, the prevalence of neovascular AMD has changed drastically. AMD was not registered in 1994 and now is the fourth-leading cause of visual disability [8], although it remains relatively low compared with Western countries [8]. …”
Section: Introductionmentioning
confidence: 99%